Organic Transistors Incorporating Lipid Monolayers for Drug Interaction Studies. Issue 3 (18th October 2019) - Cavassin, Priscila; Pappa, Anna‐Maria; Pitsalidis, Charalampos; F. P. Barbosa, Henrique; Colucci, Renan; Saez, Janire; Tuchman, Yaakov; Salleo, Alberto; Faria, Gregório C.; Owens, Róisín M.
Abstract: Cell membranes are fundamental for cellular function as they protect the cell and control passage in and out of the cell. Despite their clear significance, cell membranes are often difficult to study, due to their complexity and the lack of available technologies to interface with them and transduce their functions. Overcoming this complexity by developing simple, reductionist models can facilitate their study. Indeed, lipid layers represent a simplified yet representative model for a cell membrane. Lipid layers are highly insulating, a property that is directly affected by changes in lipid packing or membrane fluidity. Such physical changes in the membrane models can be characterized by coupling them with an electronic transducer. Herein, a lipid monolayer that is stabilized between two immiscible solvents is integrated with an organic electrochemical transistor, which is capable of operating in a biphasic solvent mixture. The platform is used to evaluate how lidocaine, a widely used anesthetic the working mechanism of which is still a matter of debate, interacts with the cell membrane. The present study provides evidence that the anesthetic directly interacts with the lipids in the membrane, affecting their packing and therefore the monolayer permeability. The proposed platform provides an elegant solution for studying compound–membrane interactions. Abstract : A platform for studying drug–cell membrane interactions is developed by coupling a lipid monolayer with an organic electrochemical transistor to readout physical changes in the membrane permeability. This platform is used to show how the local anesthetic lidocaine interacts with lipids present in mammalian cell membranes, providing evidence that the anesthetic directly affects the lipid layer packing.